Development of the talent development environment questionnaire for sport - Martindale, R. J. J.; Collins, D.; Wang, J. C. K.; McNeill, M.; Lee, K. S.; Sproule, J.; Westbury, T. (Journal of Sports Sciences, 2010)
As sporting challenge at the elite level becomes ever harder, maximizing effectiveness of the talent development pathway is crucial. Reflecting this need, this paper describes the development of the Talent Development Environment Questionnaire, which has been designed to facilitate the development of sporting potential to world-class standard. The questionnaire measures the experiences of developing athletes in relation to empirically identified "key features" of effective talent development environments. The first phase involved the generation of questionnaire items with clear content and face validity. The second phase explored the factor structure and reliability. This was carried out with 590 developing athletes through application of exploratory factor analysis with oblique rotation, principal axis factoring extraction and cronbach alpha tests. This yielded a 59-item, seven-factor structure with good internal consistency (0.616-0.978). The Talent Development Environment Questionnaire appears to be a promising psychometric instrument that can potentially be useful for education and formative review in applied settings, and as a measurement tool in talent development research.